The Implementation of PT PEMA's Corporate Social Responsibility in Supporting the Enforcement of Islamic Sharia in Aceh - Jafar, M.; Yahya, Azhari; Adli, M.; Mazwar, Mazwar; Alidar, EMK. (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
This study examines the implementation of Corporate Social Responsibility (CSR) by PT Pema within the legal framework of Aceh’s special autonomy and the application of Islamic Sharia. At both the national and regional levels, Indonesian laws and Acehnese qanun require companies operating in the natural resources sector to undertake CSR initiatives. As a regionally owned enterprise (BUMD) engaged in natural resource management and domiciled in Aceh, PT Pema is legally and morally obligated to implement CSR programs that benefit the surrounding community and environment while aligning with Islamic Sharia principles. However, the implementation of CSR at PT Pema faces various legal and practical challenges, particularly concerning regulatory consistency, governance, and conformity with Sharia values. This research employs an empirical legal approach, analyzed through the lens of Corporate Social Responsibility theory. Primary data consist of laws and regulations governing CSR, relevant Acehnese qanun, and other legal instruments related to the study. Secondary data were obtained through in-depth interviews with key informants, including academics and representatives of PT Pema. The findings reveal that the legal framework governing CSR obligations for PT Pema remains fragmented and, in some respects, contradictory, resulting in legal uncertainty. Nevertheless, PT Pema has continued to implement CSR programs in accordance with applicable legal provisions. Its CSR initiatives encompass religious, social, and economic empowerment programs, including efforts to strengthen Islamic values, enhance religious understanding, and support the construction of places of worship. These initiatives demonstrate that PT Pema’s CSR practices not only fulfill legal obligations but also contribute to supporting the implementation of Islamic Sharia in Aceh.